Desempenho financeiro de franqueados: o papel dos elementos internos da unidade franqueada e a influência da orientação para o mercado e orientação empreendedora - Nakao, Aldo Nobuyuki (2019)
Franchisors exert pressures on franchisees to ensure they follow their rules and guidelines. Franchisees with entrepreneurial orientation or market orientation are limited to act as a result of these restrictions, so there is little room for the franchisee to act within their power, which is restricted to the management of the structure of their store, which includes management of its staff and the management of its operating expenses and local publicity. Thus, it is important to understand the role of these structural elements of the store, influenced by the franchisee’s profile (entrepreneur and facing the market). Bibliometrics conducted on franchise performance confirmed that there were no studies that focused on these internal elements of the franchised unit to understand financial performance. Therefore, the purpose of this research was to explain the role of the elements under franchisee operational autonomy (staff structure and store structure) in their financial performance from the perspective of the entrepreneurial orientation profile and market orientation. After a literature review involving the conceptualization of the research constructs and approaching theories of agency, stewardship and managerial restriction, four hypotheses were presented. For this purpose, a questionnaire was submitted to 99 franchisees from the same franchise chain whose results were analyzed using descriptive statistics, confirmatory factor analysis, and structural equations modeling. Subsequently, qualitative research with seven franchisees considered key informants were conducted and analyzed through content analysis with open coding to understand the reasons that justified the parallel relations to the proposed model. The results confirmed the proposed model, pointing out that the entrepreneurial profile has a significant relation to a greater variation in the operating and advertising expenses of the store so that this variation of expenses leads to a higher financial performance of the franchisee. In turn, market orientation has a significant relationship with the franchisee’s personnel structure, so this structure is also related to the franchisee's financial performance. In addition, direct relationships of entrepreneurial orientation and market orientation with financial performance were not significant. The results point out how the franchisee’s behavior, whether market-oriented or entrepreneurial-oriented, support when they are directed to perform internal and operational activities of their franchised unit, showing that, in this way, there may be a better financial result. Considering also that the research was conducted in a franchise chain whose franchisees were not new to franchises, having more job experience, especially in the franchise chain, the theory that better explains their relationship with the franchisor is the stewardship one, showing that the agency theory loses its explanation for the franchising phenomena from some specific maturity level of the franchise chain and its franchisees.